CTE Workshop Proc. 2022
DOI: 10.55056/cte.126
|View full text |Cite
|
Sign up to set email alerts
|

Formation of professional competency in life saving appliances operation of future seafarers by means of online and simulation VR technologies

Abstract: Nowadays simulation training technology is a priority method of maritime specialists’ practical training in the world. The main purpose of using VR simulators within an educational process is to simulate work on real equipment in order to form professional competencies of seafarers. The article describes system of blended learning on the basis of Kherson State Maritime Academy, that includes alternation of traditional and online learning, virtual training by means of the VR technology, training on simulators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Voloshynov et al [50] showed an educational information system of blended learning. It includes the alternation of traditional and online learning, virtual learning using VR technology and training on simulators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Voloshynov et al [50] showed an educational information system of blended learning. It includes the alternation of traditional and online learning, virtual learning using VR technology and training on simulators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main purpose of using VR simulators within an educational process is to simulate work on real equipment in order to form professional competencies of seafarers. The article "Formation of professional competency in life saving appliances operation of future seafarers by means of online and simulation VR technologies" [246] by Serhii A. Voloshynov, Halyna V. Popova, Olena S. Dyagileva, Nataliya N. Bobrysheva and Olha V. Fedorova (figure 26) describes system of blended learning on the basis of Kherson State Maritime Academy, that l technology, training on simulators. In accordance with the principles of blended learning in Academy, there was developed an author's course "Rescue boats and life rafts specialist", which aims at providing theoretical and practical training of seafarers on launching and handling the lifeboats and liferafts and, as a result, ensures seafarers' formation of professional competency "life-saving appliances operation".…”
Section: Session 6: Immersive Technology Applications In Educationmentioning
confidence: 99%
“…The main purpose of using VR simulators within an educational process is to simulate work on real equipment in order to form professional competencies of seafarers. The article "Formation of professional competency in life saving appliances operation of future seafarers by means of online and simulation VR technologies" [243] by Serhii A. Voloshynov, describes system of blended learning on the basis of Kherson State Maritime Academy, that includes alternation of traditional and online learning, virtual training by means of the VR technology, training on simulators. In accordance with the principles of blended learning in Academy, there was developed an author's course "Rescue boats and life rafts specialist", which aims at providing theoretical and practical training of seafarers on launching and handling the lifeboats and liferafts and, as a result, ensures seafarers' formation of professional competency "life-saving appliances operation".…”
Section: Session 6: Immersive Technology Applications In Educationmentioning
confidence: 99%